PERTUMBUHAN DAN PRODUKSI BUNCIS (Phaseolus vulgaris L.) DENGAN PEMBERIAN PUPUK TANDAN KOSONG KELAPA SAWIT DAN NPK - Muhammad Yogi Saputra; Hangger Gahara Mawandha; Tantri Swandari (AGROISTA : Jurnal Agroteknologi, 2018)
The research aims to determine the effect of oil palm empty fruit bunches fertilizer and NPK and their interactions on growth and yield of beans (Phaseolus vulgaris L). The study was conducted in the garden of Education and Research Institute for Agriculture KP-2 STIPER Yogyakarta, located in the village Maguwoharjo, Depok, Sleman, Yogyakarta, Sleman regency is located at LU 734.520 - 747.050 and 1070 LS 15'03 "BB - 110028 '30" longitude at an altitude ± 112 masl. The study was conducted during ± 3 months ie from April to July 2018. This study used a factorial experiment consisting of two factors and arranged in a completely randomized design or CRD 2 factorial. The first factor is fertilizer, oil palm empty fruit bunches consisting of T0 (control), T1 (50g / polybag), T2 (75g / polybag), T3 (100g / polybag). The second factor is the NPK fertilizer consisting of N0 (Control), N1 (2.5G / polybag), N2 (5g / polybag), N3 (10g / polybag). Of the two factors obtained 4 x 4 = 16 combination of treatments, each combination is repeated 3 times, so that the total number of plants in the study 4 x 4 x 3 = 48 polybag plants. The result shows that fertilizer and oil palm empty fruit bunches NPK showed no real interaction on all the parameters are parameters plant height, number of leaves, number of branches, number of pods, pod weight and pod length. Treatment fertilizer oil palm empty fruit bunches (75g / polybag) showed good results on the parameters of the number of leaves, pods, pod weight and pod length. NPK fertilizer (2.5G / polybag) showed good results on the parameters plant height, number of leaves, pods, and pods weight, while in the pod length parameter showed good results on NPK fertilizer (5 g / polybag) based DMRT at the 5% significance level. Keywords: Growth, production, chickpeas, empty oil palm bunches fertilizer, NPK